ASOCIALS: RACE, EXCLUIDING AND ABNORMALITY IN THE STATE CONSTRUCTION IN CHILE, 1920-1960. - Fernández Labbé, Marcos (Revista de Historia Social y de las Mentalidades, 2024)
This article proposes a historical reconstruction of the institutional and discursive procesess through which the notion of asocial was articulated by the Chilean state in the early 20th century. Working on police, Law and penal sciences documentation, I explore the projects aiming to produce a familiarity with the dangerousness of a wide range of “undesirable” subjects: prostitutes, repeated criminal offenders, immigrants, vagrants, alcoholics and drug addicts. Finally, the article characterizes the opposition between social and antisocial practices as a particular mechanism of state building